Evaluation study of some professional competencies of physical and sports education teachers in secondary level from the point of view of their pupils - عبو سفيان; مهيدي محمد (sports creativity, 2025)
This study aimed at evaluating some of the professional competencies of physical education and sports professors from the point of view of their pupils, in addition to trying to find out the extent of teachers of physical education and sports awareness with knowledge and concepts related to the topics of professional competencies. In his approach to this study, the researcher relied on the descriptive method. He sampled 600 students from the secondary school (graduating classes) and 65 professors of physical and sports education in the secondary level , where the two samples were randomly selected, and the study tool consisted in a application sent to physical education professors measuring the knowledge aspect of their professional competencies, and a second one to explore the extent of implementation of their professional competencies in pupils. We came to the following conclusions: -Professors of physical education and sports are familiar with the knowledge and concepts of professional competencies topics. -Physical education and sports teachers in the secondary level apply the competencies of implementing the lesson to it large extent from the point of view of their pupils. - The physical education and sports professors of the secondary level have the competencies of personality traits from the point of view of their pupils.